2015
DOI: 10.1161/circheartfailure.114.001825
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Exercise Intolerance in Heart Failure With Preserved Ejection Fraction

Abstract: Background Exercise capacity as measured by peak oxygen uptake (Vo2) is similarly impaired in patients with heart failure with preserved ejection fraction (HFpEF) and heart failure with reduced ejection fraction (HFrEF). However, characterization of how each component of Vo2 changes in response to incremental exercise in HFpEF versus HFrEF has not been previously defined. We hypothesized that abnormally low peripheral o2 extraction (arterio-mixed venous o2 content difference, [C(a-v)o2]) during exercise signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
287
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 356 publications
(306 citation statements)
references
References 69 publications
12
287
2
5
Order By: Relevance
“…Evidence of chronotropic incompetence can be documented, 59 and abnormal oxygen extraction by the peripheral skeletal musculature, as well, 60 both of which would limit oxygen delivery to the periphery and result in symptoms of exertional intolerance. An interesting group of patients was highlighted who have almost completely normal invasive hemodynamic measures at rest (including normal brain natriuretic peptide levels) but who develop very abnormal hemodynamics only during exercise.…”
Section: Greater Appreciation Of Pathophysiologic Subsetsmentioning
confidence: 99%
“…Evidence of chronotropic incompetence can be documented, 59 and abnormal oxygen extraction by the peripheral skeletal musculature, as well, 60 both of which would limit oxygen delivery to the periphery and result in symptoms of exertional intolerance. An interesting group of patients was highlighted who have almost completely normal invasive hemodynamic measures at rest (including normal brain natriuretic peptide levels) but who develop very abnormal hemodynamics only during exercise.…”
Section: Greater Appreciation Of Pathophysiologic Subsetsmentioning
confidence: 99%
“…The same study suggests that 50% of patients with heart failure reduced ejection fraction demonstrate reduced cardiac index at rest compared with healthy controls 26. However, it appears that both heart failure patients with reduced as well as preserved ejection fraction demonstrate diminished cardiac output (cardiac index) in response to exercise‐induced stress 27, 28, 29…”
Section: Discussionmentioning
confidence: 88%
“…In support, Dhakal et al showed that peripheral oxygen extraction was lower in HFpEF compared to controls and HFrEF patients and was the major determinant of reduced exercise capacity. 16 The discrepancies in the above studies can be explained by Little and Borlaug, 9 who observed that although peripheral abnormalities were largely associated with exercise limitations, a cardiac limitation was present and could be the first and foremost underlying cause. It is also likely that common comorbidities associated with HFpEF such as pulmonary disease, obesity, and diabetes may contribute to exercise intolerance independent of the heart.…”
Section: Introductionmentioning
confidence: 99%